Catalyst-free growth of zinc nanocrystals with various morphologies on ionic liquid surfaces. Issue 44 (22nd October 2019) - Bao, Zhilong; Li, Lu; Shen, Jiawei; Ye, Xunheng; Tao, Xiangming; Yang, Bo; Ye, Gaoxiang
Abstract : We report a catalyst-free growth of zinc nanocrystals with various morphologies on ionic liquid surfaces at room temperature. Abstract : We report a catalyst-free growth of zinc nanocrystals with various morphologies on ionic liquid surfaces at room temperature. The typical width and length of the zinc nanorods and nanowires are 25–50 nm and 440–1704 nm, respectively, which are sensitive to the experimental conditions. The average size of the Zn crystal mounds with multiple concentric hexagonal terraces is around 260 nm, which increases slowly with the nominal deposition thickness and then saturates. The step thickness of the hexagonal terraces is about 18 nm. Based on the experimental results, a formation mechanism of the mounds is proposed.